2022
DOI: 10.1097/j.pain.0000000000002750
|View full text |Cite
|
Sign up to set email alerts
|

A paraventricular hypothalamic nucleus input to ventral of lateral septal nucleus controls chronic visceral pain

Abstract: Supplemental Digital Content is Available in the Text. Paraventricular hypothalamic CaMKIIα-positive neurons input to ventral of lateral septal CaMKIIα-positive neurons controls chronic visceral pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Given its location and connections, the lateral septal nucleus forms a critical part of the limbic system, integrating a variety of emotional and cognitive information to regulate behavioral responses, reward, feeding, anxiety, fear, and sociability ( Rizzi-Wise and Wang 2021 ). It is therefore not surprising that it also has a role in pain, with the circuit from the paraventricular hypothalamus to the lateral septal region being identified as necessary and sufficient for regulating visceral pain ( Li et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given its location and connections, the lateral septal nucleus forms a critical part of the limbic system, integrating a variety of emotional and cognitive information to regulate behavioral responses, reward, feeding, anxiety, fear, and sociability ( Rizzi-Wise and Wang 2021 ). It is therefore not surprising that it also has a role in pain, with the circuit from the paraventricular hypothalamus to the lateral septal region being identified as necessary and sufficient for regulating visceral pain ( Li et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, neural circuits formed by glutamatergic neurons with other glutamatergic neurons modulate sleep–wake cycles, cognitive impairments, and learning and memory deficits 41–43 . In addition, our research has previously shown that other brain circuits glutamatergic neurons form neural circuits with glutamatergic neurons that modulate visceral pain 27,44 . In this study, viral tracing results revealed that excitatory neurons in the PVT projected to the IC excitatory neurons.…”
Section: Discussionmentioning
confidence: 52%
“…Fiber photometry is widely used to detect and record neuronal calcium activity based on fluorescent calcium indicator. GCaMP has an exceptionally high sensitivity to calcium ions and thus effectively indicates changes in calcium activity through instantaneous changes in fluorescence signal intensity 25–27 . To assess the calcium ion activity of glutamatergic neurons in the IC, at the sixth week after birth, AAV2/9‐vglut2‐GCaMP6s (BrainVTA, Wuhan, China) virus was injected into the IC region of both NCI and CON group mice (150 nL per injection).…”
Section: Methodsmentioning
confidence: 99%
“…The population of glutamatergic neurons in VTA is reported to be less than other types of neurons like GABA and DA, and we only wanted these glutamatergic projections to be NAc-specific rather than VTA glutamatergic projection to other brain regions in VGluT2-Cre mice. We used the CaMKII tracing method in the wild-type mice because CaMKII was reported to colonize predominantly with the glutamate neurons ( Zhu et al, 2014 ; Basting et al, 2018 ; Liu et al, 2020 ; Sheng et al, 2020 ; Zhang et al, 2020 ; Li et al, 2022 ). For this, a retrograde CaMKIIa-CRE viral vector was injected into the NAc, and DIO-EYFP was injected in the VTA of the wild-type mice ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 99%